SISTEM PENGENDALIAN INTERNAL DAN PERAN AUDIT INTERNAL TERHADAP PENCEGAHAN KECURANGAN - Karlina Ghazalah Rahman (Bongaya Journal for Research in Accounting (BJRA), 2020)
The aim of this research to analyze the effect internal control system which include internal environment, risk assesment, internal activity, information and communication, and evaluating internal control and audit internal role to fraud prevention of Makassar City. Data in this research were obtained from observation and questionnaires that distributed to respondents. Multiple Linier Regression formula was used in this study with SPSS software. The test result of multiple linier regression indicated that internal control system and audit internal role positively effect the fraud prevention of Makasssar City. This research was conducted at 31 OPD (Local Government) in Makassar City.